Esse est percipi w interpretacji Berkeleya : komentarz ontologiczny - Bastek, Adam (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The paper presents consequences of famous Berkeley's interpretation of being and thinking and their ontological connection. At the same time it constitutes an attempt to find an answer to one of the most important ontological questions about immediateness of our knowledge. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Nauki Humanistyczne (10); 2006; nr 1149, s. 21-34